Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173661
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Human Cognition and Visual Behavior on Password Strength during Picture Password Composition

Abstract: Visual attention, search, processing and comprehension are important cognitive tasks during a graphical password composition activity. Aiming to shed light on whether individual differences on visual behavior affect the strength of the created passwords, we conducted an eye-tracking study (N=36) and adopted an accredited cognitive style theory to interpret the results. The analysis revealed that users with different cognitive styles followed different patterns of visual behavior which affected the strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Imagers outperformed Verbals (Belk et al, 2013a) and field-independent individuals outperformed field-dependent individuals (Belk et al, 2017a) in login tasks when using a recognition-based GUA scheme. Katsini et al (2018b) revealed that field-independent individuals created stronger passwords when using a recall-based GUA scheme than field-dependent individuals.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Imagers outperformed Verbals (Belk et al, 2013a) and field-independent individuals outperformed field-dependent individuals (Belk et al, 2017a) in login tasks when using a recognition-based GUA scheme. Katsini et al (2018b) revealed that field-independent individuals created stronger passwords when using a recall-based GUA scheme than field-dependent individuals.…”
Section: Related Workmentioning
confidence: 99%
“…However, considering that the strength of the chosen graphical password is determined during password composition, it is important to investigate the effect of individual cognitive differences in the registration phase. In this regard, Katsini et al (2018b) revealed that human cognitive styles influence the graphical password choices when using a recall-based GUA scheme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' knowledge, DeCACHe is the first attempt for supporting CH designers in creating cognition-centered adaptive activities. While DeCACHe, in its current implementation, aims to support designers within the CH domain, it could be expanded to other domains, where there is evidence that cognitive characteristics have an impact on the users' experience, such as e-learning [75], gaming [76], security [77], business and management [78], and e-commerce and marketing [79]. For example, in their recent work, Katsini et al [80] revealed that individuals who are characterized as field-dependent tend to have a more limited password key-space compared to individuals who are characterized as field-independent when creating a graphical password.…”
Section: Implications Beyond the Ch Domainmentioning
confidence: 99%
“…From an end-user perspective, evidence has shown that user preference and task performance in textual and graphical passwords vary significantly depending on the user and the context of use, suggesting that any specific solution might not please everyone [14]. In particular, research has shown that users with different age [15], cognitive disabilities [16], cognitive abilities [17] prefer and perform differently in textual and graphical passwords. From the technology perspective, studies indicate that the device type, such as touch screens, hand gestures, etc.…”
Section: Introductionmentioning
confidence: 99%